PENGGUNAAN INTERNET DI KALANGAN MAHASISWA JURUSAN BIMBINGAN DAN KONSELING FAKULTAS ILMU PENDIDIKAN DI UNIVERSITAS NEGERI PADANG - Yunelti, Febrida (Konselor, 2013)
Internet usage among students, should be used according to the needs of education being pursued. Phenomena in the field indicate that there are students who do not use the Internet in accordance with the educational needs being passed. This study considered descriptive quantitative research aimed at uncovering the type of data it is about the use of the Internet among students. This study population is students of Department of Guidance and Counseling in the UNP. The results showed that of the three aspects of Internet usage, the overall use of the Internet for learning aspect is an aspect that frequently used by students.